2017
DOI: 10.1021/acs.jmedchem.6b01541
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of LX2761, a Sodium-Dependent Glucose Cotransporter 1 (SGLT1) Inhibitor Restricted to the Intestinal Lumen, for the Treatment of Diabetes

Abstract: The increasing number of people afflicted with diabetes throughout the world is a major health issue. Inhibitors of the sodium-dependent glucose cotransporters (SGLT) have appeared as viable therapeutics to control blood glucose levels in diabetic patents. Herein we report the discovery of LX2761, a locally acting SGLT1 inhibitor that is highly potent in vitro and delays intestinal glucose absorption in vivo to improve glycemic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 52 publications
4
43
0
Order By: Relevance
“…Current clinical trials are investigating the use of mizagliflozin as a potential candidate to improve functional constipation (due to its ability to increase luminal glucose and water content) . In addition, newly developed non‐absorbable SGLT1 inhibitors include LX2761 and TP0438836 (Table ). Both compounds significantly reduced blood glucose excursions in response to oral glucose tolerance tests in rodents.…”
Section: Development Of Sglt Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Current clinical trials are investigating the use of mizagliflozin as a potential candidate to improve functional constipation (due to its ability to increase luminal glucose and water content) . In addition, newly developed non‐absorbable SGLT1 inhibitors include LX2761 and TP0438836 (Table ). Both compounds significantly reduced blood glucose excursions in response to oral glucose tolerance tests in rodents.…”
Section: Development Of Sglt Inhibitorsmentioning
confidence: 99%
“…Inevitably, blocking glucose transport in the upper small intestine will lead to a greater glucose delivery to further distal segments of the small intestine and colon . It has been speculated that the gut microbiome metabolizes glucose in the colon to form SCFA, which bind to free fatty acid receptors (FFAR2/3) on distal small intestine L cells and may promote sustained GLP‐1 release.…”
Section: Intestinal Sglt1 Inhibition: What Does It Add?mentioning
confidence: 99%
“…In this context, the development of straightforward, modular,a nd operationally simple conditions to access Carylated saccharides remains an unsolved challenge,a nd methods that would preserve the anomeric carbon to afford non-classical, "reverse aryl C-glycosides" are particularly scarce.I ndeed, despite the attractive biological properties of these compounds, [11] few synthetic efforts have been carried out in this regard. [12] Other approaches toward the synthesis of reverse aryl Cglycosides have been reported, such as the [4+ +2] cycloaddition between Danishefskysd ienes and aromatic aldehydes,y ielding glycal derivatives, [13] or the addition of organozinc reagents to 4a-epoxypyranosides (Scheme 2).…”
mentioning
confidence: 99%
“…We are developing LX2761, a compound restricted to the intestinal lumen where it inhibits SGLT1, to provide a therapeutic option for people with diabetes that improves their glycemic control with minimal systemic side effects and adequate gastrointestinal tolerability. In our initial report (Goodwin et al, 2017), we showed that LX2761 inhibits SGLT1 and SGLT2 with IC 50 values of 2.2 and 2.7 nM, respectively. Consistent with being designed to have poor oral bioavailability, LX2761 had extremely low systemic exposure after oral administration to healthy mice and was unable to appreciably increase UGE by inhibiting renal SGLT2; in contrast, sotagliflozin administered orally to healthy mice at the same dose had excellent systemic exposure and markedly increased UGE.…”
Section: Introductionmentioning
confidence: 90%
“…,5-trihydroxy-6-(methylthio)tetrahydro-2H-pyran-2-yl)benzyl)phenyl)butanamide; LP-945013, (2S,3R,4R,5S,6R)-2-(3-(4-(3-((1-hydroxy-2-methylpropan-2-yl)amino)propoxy)benzyl)-4-methylphenyl)-6-(methylthio)tetrahydro-2H-pyran-3,4,5-triol; and sotagliflozin were synthesized at Lexicon Pharmaceuticals (Goodwin et al, 2008;Zambrowicz et al, 2012;Carson et al, 2014;Goodwin et al, 2017); LP-945013 has also been referred to as compound 7 (Goodwin et al, 2017). In all in vivo studies presented here, LX2761, LP-945013, and sotagliflozin were administered by oral gavage in a volume of no more than 10 ml/kg, and the vehicle was always aqueous 0.1% v/v Tween 80.…”
Section: Methodsmentioning
confidence: 99%